Optimalisasi Teknologi Pakan Lokal Dengan Pengolahan Jerami Jagung Di Desa Klambir Lima Kebun - Dini Julia Sari; Sri Setyaningrum; Warisman warisman (STMIK Royal, 2022)
Abstract : Klambir Lima Kebun Village has excellent potential in the form of availability of agricultural land and livestock, as a center for beef cattle development, large amounts of agricultural waste such as corn straw and the majority of the community work as plantation employees, farming and raising livestock. The abundant corn straw in the village of Klambir Lima Kebun can be stored and used when there is a shortage of green fodder, such as a long dry season. To maintain the stability of animal feed, it is necessary to optimize local feed technology by processing fermented corn straw and silage which aims to determine the potential of fermented corn straw and silage which can be used as ruminant animal feed and to determine the capacity of livestock from the potential of fermented corn straw and silage in village of Klambir lima Kebun, Hamparan Perak, Deli Serdang. The implementation method used in this community service is a training method which will then be followed by discussions and hands-on practice on the manufacture of fermented corn straw and silage as well as direct feeding of fermented corn straw and silage to livestock. The results of the activity show that the village of Klambir Lima Kebun has the potential to produce ruminant feed based on local agricultural waste, namely corn straw.Keywords: corn straw; fermentation; silage; feed; livestock Abstrak : Desa Klambir Lima Kebun memiliki potensi unggulan berupa tersedianya lahan pertanian dan peternakan, sebagai sentra pengembangan ternak sapi potong, banyaknya limbah pertanian contohnya jerami jagung dan mayoritas masyarakat bekerja sebagai karyawan perkebunan, bertani dan beternak. Jerami jagung yang melimpah di desa Klambir Lima Kebun dapat disimpan kemudian digunakan pada saat kekurangan pakan penghijauan seperti musim kemarau panjang. Untuk menjaga kestabilan pakan ternak dibutukan optimalisasi teknologi pakan lokal dengan pengolahan jerami jagung fermentasi dan silase yang bertujuan untuk mengetahui potensi dari jerami jagung fermentasi dan silase yang dapat dimanfaatkan sebagai pakan ternak ruminasia dan mengetahui kapasitas tampung ternak dari potensi jerami jagung fermentasi dan silase di desa Klambir lima Kebun, Hamparan Perak, Deli Serdang. Metode pelaksanaan yang digunakan dalam pengabdian masyarakat ini adalah metode pelatihan yang selanjutnya akan dilanjutkan dengan diskusi serta praktek langsung tentang pembuatan jerami jagung fermentasi dan silase serta pemberian langsung jerami jagung fermentasi dan silase pada ternak. Hasil kegiatan diketahui bahwa desa Klambir Lima Kebun sangat berpotensi menghasilkan pakan ternak ruminansia berbasis limbah lokal pertanianya yaitu jerami jagung.Kata kunci: fermentasi; jerami jagung; pakan; silase; ternak.